2013
DOI: 10.1093/ije/dyt154
|View full text |Cite
|
Sign up to set email alerts
|

The association of pattern of lifetime alcohol use and cause of death in the European Prospective Investigation into Cancer and Nutrition (EPIC) study

Abstract: Limiting alcohol use throughout life is associated with a lower risk of death, largely due to cardiovascular disease but also other causes. However, the potential health benefits of alcohol use are difficult to establish due to the possibility of selection bias and competing risks related to diseases occurring later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 31 publications
12
112
3
4
Order By: Relevance
“…18,50-52 Flawed study designs have been implicated in earlier findings of "protective effects" 53-58 -however, a great deal of controversy on this topic remains. 51,55,[59][60][61][62] A large proportion of participants in this study reported light-moderate drinking (0.1 to 29.9 g of ethanol/day or < 1 to 2 drinks/day), and may be unaware of the potential harm associated with even small Continued on the following page but regular amounts of alcohol. Further investigation into the relationship between low-risk drinking and health outcomes is essential to better characterize the exact risk-benefit threshold for alcohol consumption among different population groups.…”
Section: Discussionmentioning
confidence: 91%
“…18,50-52 Flawed study designs have been implicated in earlier findings of "protective effects" 53-58 -however, a great deal of controversy on this topic remains. 51,55,[59][60][61][62] A large proportion of participants in this study reported light-moderate drinking (0.1 to 29.9 g of ethanol/day or < 1 to 2 drinks/day), and may be unaware of the potential harm associated with even small Continued on the following page but regular amounts of alcohol. Further investigation into the relationship between low-risk drinking and health outcomes is essential to better characterize the exact risk-benefit threshold for alcohol consumption among different population groups.…”
Section: Discussionmentioning
confidence: 91%
“…Les effets nocifs de la consommation d'alcool sur la santé pourraient être sous-estimés par rapport à ceux découlant du tabagisme : on a estimé qu'en 2000 l'alcool avait entraîné une charge mondiale de morbidité semblable à celle du taba gisme 8,48 . Les résultats récents en recherche ne montrent pas que la consommation d'alcool aurait des effets protecteurs sur l'organisme 18, [50][51][52] et certaines études antérieures ayant étayé l'existence d'« effets protecteurs » de la consommation d'alcool étaient défaillantes sur le plan méthodologique [53][54][55][56][57][58] -en fait, ce sujet demeure controversé 51,55,[59][60][61][62] . Une grande proportion de participants à l'étude ont indiqué consommer de l'alcool en quantité faible ou modérée (0,1 à 29,9 g d'éthanol par jour ou de moins de 1 verre par jour à 2 verres par jour) et pourraient ne pas être conscients des effets néfastes potentiels de quantités d'alcool dans l'organisme certes faibles mais régulières.…”
Section: Habitudes De Consommation D'alcoolunclassified
“…Findings from meta-analyses have shown considerably elevated relative risks in former drinkers, equivalent to 30 g of pure alcohol per day or more for some outcomes, 94,95 although this fi nding could occur as a result of confounding by misclassifi cation of former drinkers as lifetime abstainers. [96][97][98][99] Future GBD studies should carefully re-evaluate whether or not the excess risk in former drinkers is overestimated. If the relative risks for former drinkers have been overestimated, this overestimation will also aff ect our assessment of the alcohol SEV and the global trend in the SEV.…”
Section: Alcohol Usementioning
confidence: 99%